2008
DOI: 10.2117/psysoc.2008.157
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Participation Motivation to Goal Orientations and Perceived Physical Ability in Brazilian Swimmers

Abstract: The relationships of achievement participation motivation, goal orientations and perceived physical ability were investigated in young competitive Brazilian swimmers. Four hundred and twenty five swimmers (287 males and 138 females, ranging in age from 11 to 25 years) completed the Participation Motivation Inventory (PMI), the Task and Ego Orientation in Sport Questionnaire (TEOSQ), and the Perceived Physical Ability Scale (PPA). Findings provided evidence for the validity and reliability of the questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…Similarly, Zahariadis and Biddle (2000) reported that ego orientation was positively and highly correlated with status/recognition motives. However, the results of another study (Andrade et al, 2008) showed that ego orientation predicted motive for participation and was related to status. Duda (1989) reported that ego orientation was positively correlated with the competitiveness and social status subscales.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Zahariadis and Biddle (2000) reported that ego orientation was positively and highly correlated with status/recognition motives. However, the results of another study (Andrade et al, 2008) showed that ego orientation predicted motive for participation and was related to status. Duda (1989) reported that ego orientation was positively correlated with the competitiveness and social status subscales.…”
Section: Discussionmentioning
confidence: 90%
“…In their study, Altintas, Hacioglu, Sagturk, Belman, and Asci (2010) found that task orientation was a significant predictor of the skill development motive for young soccer players. Results gained in other studies have indicated that task orientation is related to team atmosphere motives, status/recognition motives (Zahariadis & Biddle, 2000), competition motives (Andrade, Salguero, Gonzalez-Boto, & Márquez, 2008;White & Duda, 1994), and fitness and team membership (White & Duda, 1994). If it is taken into account that task-oriented individuals are more focused on learning and mastering new skills (Boyd, Weinmann, & Yin, 2002) and are more intrinsically motivated (Brunel, 1999;Jagacinski & Strickland, 2000;Kavussanu & Roberts, 1996), the findings in our research are inconsistent with the literature.…”
Section: Discussionmentioning
confidence: 97%
“…El TEOSQ ha mostrado una adecuada validez y fiabilidad en diferentes países al usarse en contextos deportivos (e.g., Cindi & Koenraad, 2005;De Andrade, Salguero, González-Boto & Márquez, 2008;Li, Harmer, Chi & Vongjaturapat, 1996;Wakayama et al, 2002). Como hemos mencionado anteriormente, en un contexto español de EF, la herramienta muestra también adecuadas propiedades psicométricas (Peiró & Sanchis, 2004).…”
Section: Generalización Interculturalunclassified
“…Research in the area of participation and motivation in physical education has linked elements such as fun, skill ability and confidence to participants' willingness to engage in physical activity (Andrade, Salguero, Gonzalez-Boto, & Márquez, 2008); hence, it is imperative that today's youth are engaged and encouraged in physical activities that have a direct beneficial connection to their overall quality of life. For a large segment of the population, aquatic physical activities (APA; e.g., snorkeling or diving, water walking, competitive and instructional swimming, aquatic fitness, aquatic sports, water aerobics, smallcraft aquatic activity) comprise one of the more popular/common recreational activities (CDC, 2012).…”
Section: Angela Bealementioning
confidence: 99%